Instrumen Penilaian Pembelajaran Afektif dalam Membentuk Karakter Siswa - Fifi Wardatusshopa; Inayatul Ummah; Enung Nugraha; Abdul Mu’in (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Affective assessment instruments are an important component in education which aims to measure aspects of students' attitudes or behavior, which includes spiritual and social attitudes. Based on Government Regulation Number 19 of 2005 concerning National Education Standards, as well as Law Number 20 of 2003 concerning the National Education System, learning assessment must include aspects of attitude (affective), knowledge (cognitive), and skills (psychomotor). The type of research used in this research is qualitative research using the Library Research method or a research method that uses theories from books that support and are relevant to affective learning assessment instruments in shaping student character. The research results show that choosing the right learning instruments, especially in the affective domain, really helps teachers in shaping students' character, so that they can improve the quality of the learning process and learning outcomes as an improvement in the quality of education. The attitude scale models that can be used include the Bogardus Scale, Thurstone Scale, Guttman Scale, and Likert Scale